What can corpora do better than other digital tools? Corpus-based language learning for specific purposes (LSP) in German as a Foreign Language (GFL), using the example of legal language - Kontutytė, Eglė (Kalbotyra, 2025)
Corpora are being increasingly used as a digital medium for language work in practical environments and, consequently, as a digital learning tool in foreign language learning. This has given rise to the relatively new area of corpus didactics within media pedagogy for German as a Foreign Language.This article explores the possibilities of the corpus-based approach to learning languages for specific purposes and its potential advantages in comparison to other digital tools, with a particular focus on legal language. The corpus GeLeCo (German Legal Corpus) is used to illustrate corpus-based methods in LSP didactics.By using the example of intertextual markers in court decision, the study investigates whether and in what ways corpora might offer advantages over machine translation tools and AI chatbots when translating legal texts. The analysis of linguistic means in the corpus GeLeCo shows that the linguistic means used in court decisions to reference other legal texts differ in frequency from those produced by translation engines.These findings provide the foundation for didactic considerations and the development of teaching scenarios and tasks designed to raise awareness of learners in law-related GFL learning of the limitations of automated translation tools and chatbots. While such tools might roughly reproduce the general content of a legal text, they often fail to capture the nuanced legal formulations that are critical for professional legal communication.